Reviews of Books (International review of mission, 1955)
Book reviewed in this article: CHRISTIANITY AT THE THRESHOLD: A History of Christianity. By Kenneth Scott Latourette. THE SIGNIFICANCE OF PAST EVENTS: A History of the London Missionary Society 1895–1945. By Norman Goodall. THE DETERMINING POWER OF RELIGION: The Living Christ and Dying Heathenism. The Experiences of a Missionary in Animistic Heathendom. By Joh. Warneck. EPISCOPACY IN THE OECUMENICAL DEBATE: The Historic Episcopate in the Fullness of the Church: Seven Essays by Priests of the Church of England. Edited by Kenneth M. Carey. CHANGES IN MISSIONARY THINKING: Revolution in Missions. By Willis Church Lamott. MISSIONS TO THE LAPPS: Samenes Kristning og Finnemisjonen til 1888. By Adolf Steen. ARE THERE ANY CHANGES IN JUDAISM?: Wandlungen im Judentum. By Gerhard Jasper. THE CHRISTIAN STUDENTS' LIBRARY: The Christian Doctrine of Salvation. By Sigfrid Estborn. Madras: The Christian Literature Society. Rs 3.12.0. 1954.: The Revelation of St John the Divine. By Anthony T. Hanson. Madras: The Christian Literature Society. Re 1.2.0. 1954.: The History of the Reformation. By H. C. Lefever. EARLY RHODESIAN HISTORY: The Southern African Diaries of Thomas Leask: 1865–1870. (Central African Archives, Oppenheimer Series, No. 8.) Edited by J. P. R. Wallis. THE CHALLENGE OF THE CAPE VERDE ISLANDS: Ultramar Portugues. Volume 2: Ilhas de Cabo Verde. By António Mendes Corrêa. CUSTOMARY LAW IN THE SUDAN: A Manual of Nuer Law. By P. P. Howell. AN EMERGING PATTERN IN RELIGIOUS EDUCATION: Religious Education in Schools